Resonance enhanced THz generation in electro-optic polymers near the absorption maximum - Sinyukov, Alexander M.; Leahy, Megan R.; Hayden, L. Michael; Haller, Marnie; Luo, Jingdong; Jen, Alex K-Y.; Dalton, Larry R. (AIP Publishing, 2004)
The electro-optic (EO) coefficient of an organic nonlinear material exhibits a sharp resonance near the absorption maximum of the material. Due to this resonance, we experimentally observe the amplitude of the THz field generated from a 3.1-𝜇m-thick EO polymer composite to be larger than that emitted from a 1000-𝜇m-thick crystal of ZnTe. This comparison allows us to estimate the resonance enhanced EO coefficient of the polymer composite to be over 1250pm∕V at 800nm